2018
DOI: 10.14814/phy2.13634
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of cardiovascular control and function following incomplete T3 and T10 spinal cord injury in rodents

Abstract: Spinal cord injury (SCI) is a devastating condition that results in whole‐body dysfunction, notably cardiovascular (CV) disruption and disease. Injury‐induced destruction of autonomic pathways in conjunction with a progressive decline in physical fitness contribute to the poor CV status of SCI individuals. Despite the wide use of exercise training as a therapeutic option to reduce CV dysfunction, little is known about the acute hemodynamic responses to the exercise itself. We investigated CV responses to an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…Interestingly, the vulnerability to sympathetic stimulation in rodents with contusive SCI using this injury model was shown to be associated with adverse changes in left ventricular function and blunted responses to DOB based on echocardiographic markers of cardiac dysfunction at 1week after injury, but with an exaggerated response 5 weeks after SCI (Harman et al, 2018). In the present study, we observed changes to ECG parameters with DOB as early as 1-week post injury, suggesting that cardiac electrical remodeling occurs prior to structural remodeling.…”
Section: Dob Further Exacerbated the Adverse Effects Of Sci On Ecg Parameterssupporting
confidence: 52%
“…Interestingly, the vulnerability to sympathetic stimulation in rodents with contusive SCI using this injury model was shown to be associated with adverse changes in left ventricular function and blunted responses to DOB based on echocardiographic markers of cardiac dysfunction at 1week after injury, but with an exaggerated response 5 weeks after SCI (Harman et al, 2018). In the present study, we observed changes to ECG parameters with DOB as early as 1-week post injury, suggesting that cardiac electrical remodeling occurs prior to structural remodeling.…”
Section: Dob Further Exacerbated the Adverse Effects Of Sci On Ecg Parameterssupporting
confidence: 52%
“…Unlike arm ergometry, swimming involves a significant need for trunk stability/orientation to ensure that the rodent swims in the appropriate direction during each lap. Previous studies in our lab showed that 4 min of swim exercise significantly challenges the CV system following incomplete T3 contusion in female rats (Harman et al, 2018). The current results suggest that intensive swimming exercise rehabilitation may tend to normalize resting hemodynamic parameters in animals with severe T2 contusions.…”
Section: Active Swimming Exercisesupporting
confidence: 60%
“…Spinal cord injury results from central nervous system trauma and seriously endangers human health. This major cause of disability imposes a heavy economic and social burden ( Jain et al, 2015 ; Harman et al, 2018 ; Zhou et al, 2018 ). Various drugs and cell therapies have shown some potential in the treatment of spinal cord injury, and some clinical trials have shown promising results.…”
Section: Introductionmentioning
confidence: 99%